Corporate Governance and Firm Efficiency: An Application of Internet Companies of China - Shabbir, M.F. (Routledge, 2020)
This study analyzes the impact of corporate governance on firm efficiency. The recent trend to measure performance from efficiency ratios has received attention due to its realistic approach. However, empirical evidence to prove a significant relationship between corporate governance and firm efficiency is lacking. We study panel data on 2,823 firm-year observations of Chinese internet companies from 2005 to 2017, using data envelopment analysis with variable return to scale technology to measure efficiency. The efficiency scores of companies are then regressed on corporate governance variables to measure the effect on technical efficiency. Furthermore, fuzzy-set qualitative comparative analysis (QCA) analysis used to provide a deep empirical understanding of the phenomenon. This study contributes to the existing body of knowledge in two ways by providing a strategic framework for exploring the governance-efficiency relation by providing empirical evidence. In addition, this study uses multiple methodological approaches to provide useful insights into corporate governance and efficiency. Â© 2020 Taylor & Francis Group, LLC.